Kedudukan Hukum dalam Lingkungan Masyarakat - Tamaulina Br. Sembiring; Yohana Riama Theresia Br. Tampubolon; Yehezkiel Panjaitan; Rahmi Elma Rizky (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Law is a set of rules that regulate the behavior of individuals and groups in society to create order and justice. In the context of society, legal status not only functions as a means to regulate relations between individuals, but also as a tool to maintain the sustainability of social, political, and cultural values. This article will discuss the legal status in society, both theoretically and practically, and how law interacts with social and cultural structures in creating the desired order.